Lecture Methods During the New Normal Era - Irianto Aras; Sitti Hardiyanti Arhas (Universitas Negeri Makassar, 2022)
The implementation of Distance Learning for 2 years, caused students to miss the school atmosphere because they were used to using smartphones in the learning process, but when the Covid-19 atmosphere began to be under control, the learning process was carried out again in the classroom, therefore schools had to make changes. changes in the learning process. This study aims to determine the use of the lecture method during the new normal era in performing administrative procedures subject at SMK Negeri 1 Bone. This study uses a qualitative descriptive approach. There were 7 informants in this study. Data collection is done through interview techniques and observation. The results of the study indicate that the implementation of the lecture method begins with preparation, namely praying together to avoid Covid-19, conveying learning objectives, and doing apperception. The implementation of learning is directed so that students stay focused on the learning atmosphere, with the focus on students, the learning objectives will be easily achieved. The final stage is carried out with a question and answer session, and concluding, not forgetting that the teacher always reminds students to continue to implement health protocols.